Japanese Cultural thought Patterns as Manifested in English Emails - Andika Paramita; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2014)
Cultural thought patterns and their underlying principles as manifested in English email should be understood earlier for both email sender and recipient. The main goal is to prevent from misunderstanding or miscommunication caused of different cultures and linguistic knowledge. This study was conducted to find the Japanese Cultural Thought Patterns as Manifested in English Emails and their underlying principles as well. The primary data were collected from English emails written by native Japanese with different background of works who were able to write English emails.